Formation of Virtues and Skills in Children in Family Education by Parents - Baydjanova Iroda Abdullaevna (Zien Journals, 2022)
This article analyzes difficult moments in the life of children, when they must be sure of the support and understanding of their parents. Parents should be the closest friends for their children, understanding the complexity and inconsistency of their inner world, and building their relationships with children on the basis of this understanding.
Keywords: Mother; child; respect, care; rude words and actions